Pengaruh Good Zakat Governance dan Pengendalian Internal Terhadap Akuntabilitas terhadap Akuntabilitas Laporan Keuangan pada Unit Pengumpul Zakat di Kabupaten Purbalingga - Febrianing, Brina (Indonesian Journal of Islamic Business and Economics (IJIBE), 2020)
The aim of this study is to determine effect of Good Zakat Governance and Internal Control on Financial Report Accountability of Zakat Collection Unit in Purbalingga Regency. The population in this study is all zakat management organizations in UPZ form and registered in BAZNAS Purbalingga Regency, this study use simple random sampling, 41 zakat management organizations are taken. The data is analyzed by multiple linear regression analysis techniques. The results of this study indicate that: (1) Good Zakat Governance affects the accountability of financial reports; (2) Internal control does not affect the accountability of financial reports of zakat management organizations in Purbalingga Regency. The implication of this study is the accountability of financial reports on Zakat Collection Unit in Purbalingga Regency can be increased by taking into account several influencing factors such as Good Zakat Governance and internal control, by increasing the ability of human resources by training.